İlköğretim 3. sınıf öğrencilerinin okuduğunu anlama becerilerinin geliştirilmesinde gösteri (demonstrasyon) yönteminin etkililiğinin incelenmesi - Çelikçi, Serap (My University, 2000)
derslerde başarılı olmaktadırlar. O halde başarılı olmanın sırrı, okuduğunu anlamaktan geçmektedir. Öğrencilerin başarı seviyelerini yükseltmek için onlara, okuduğunu anlama gücü kazandırılmalıdır. Bu da derste kullanılan yöntemlerin etkililik derecelerine bağlıdır. Okuduğunu anlamayı oluşturmada en etkili yöntemi bulmak gerekmektedir. Bu araştırmada öğrencilerin okuduklarını anlamaları için, gösteri yöntemi esas alınmış ve üzerinde birçok çalışmalar yapılmıştır. Araştırmanın literatürünü oluşturan bölümünde; okuma, önem ve amacı, okumanın çeşitli yönleri ele alınmıştır. Yine bu bölümünde; anlama, amaç ve önemi, anlamaya etki eden faktörler, okuduğunu anlama, okuma hızı ve anlama, anlama gücünün geliştirilmesi üzerinde durulmuştur. Son olarak; gösteri (demonstrasyon) yöntemi, yararları ve sınırlılıkları, etkili kullanımı, resimle anlatım, resimlerin özellikleri açıklanmıştır. Araştırmanın uygulama kısmı; 1999-2000 öğretim yılında İstanbul ili Esenler ilçesine bağlı Tacirler Eğitim Vakfı İlköğretim Okulunun üçüncü sınıf öğrencileriyle gerçekleştirilmiştir. Uygulamaya 100 öğrenci katılmıştır. Bu 100 öğrenciyle önce gösteri (demonstrasyon) yöntemi ve klasik yöntemlerle metin işlenmiş, daha sonra Okuduğunu Anlama Becerisi Başarı Düzeyi Testi uygulanmıştır. Uygulanan bu test ile Türkçe derslerinde kullanılan gösteri (demonstrasyon) yöntemi ve resimlerin, okuduğunu anlamada başarı düzeyini ne şekilde etkilediği ölçülmeye çalışılmıştır. Kişisel Bilgi Formundan elde edilen veriler üzerinde varyans analizi, frekans-yüzde ve t testi hesaplamaları yapılmıştır. Uygulama sonunda, Türkçe öğretiminde, okuduğunu anlamada gösteri (demonstrasyon) yöntemi kullanılarak öğretim yapılan deney grubu ile günümüzdeki klasik uygulamalara göre öğretim yapılan kontrol grubunun okuduğunu anlama becerisindeki başarı ortalamaları arasındaki fark .01 düzeyinde anlamlı çıkmıştır. Bu çalışma ile gösteri (demonstrasyon) yöntemi ve resimle anlatımın okuduğunu anlamada etkili olduğu sonucuna varılmıştır.

The importance of reading in life of human has been emphasized since old times. Reading has been assumed as a basic supply which develops thought. The education of reading takes part importantly in topics of prime school. Reading and writing which are taught in first-class change to a skill in next times. Basic stones of education are reading and understanding what we read. The students who understand what they read truly, quickly and exactly succeed not only in Turkish lesson but also in the other lessons. So the key of success is understanding what we read. The students should be gained the skill of understanding what they read to increase their level of succes. This is dependent on efficiency of methods which are used in lessons. Finding the most effective method is necessary in understanding what we read. Method has been given priority in this research for students to understand what they read. For that reason a lot of studies have been done. In the first part of research reading, importance and aim of reading, different aspects of reading have been discussed. In the second part, understanding, aim and importance of understanding, factors which affect understanding, developing the skill of understanding have been emphasized. In the third part, the method of demonstration, its benefits and limits, using of it effectively, the expression by means of pictures, features of pictures have been explained. The part of practice of this research has been realized with students in third class in the Tacirler Elementry School which is included Esenler in İstanbul in 1999-2000 education years A hundred students have taken part in this practice. Firstly these students have been explained the text by means of the method of demonstration, then they have been given the test of level of success-the skill of understanding what is read. Whether the method of demonstration and pictures which are used in Turkish lessons affect the level of success in understanding what is read has been tried to learn with this test. On datums which have been obtained from the Form of Personal Information, frequency-percentage, the analyze of variance and calculations of t-test have been done. At the end of this practice the difference between the averages of the group which has been educated by means of the method of demonstration in Turkish education and the group of control which has been educated by means of classic methods in today is at the level of .01. That the method of demonstration and explanation by means of pictures are effectivein understanding what is read has been drawn a conclusion with this study.
Keywords: İlköğretim; ÖĞRENCİLER-İLKÖĞRETİM